PENGARUH STRUKTUR KEPEMILIKAN ASING DAN KUALITAS AUDIT TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI MEDIASI - Sri Hardyanti Budiman; Fransiskus Randa; Bernadeth Tongli (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2021)
This study aims to examine the effect of foreign ownership structure and audit quality on firm value with earnings management as mediation. The population used in this study are all companies listed on the Indonesia Stock Exchange (IDX) with the research period of 2013-2018. The method of determining the sample using non-random sampling i.e purposive sampling and uses secondary data in the form of annual reports and financial statements of the company. The analytical methods used are path analysis and simultaneous test (F test). The results showed that the foreign ownership structure has a negative and significant effect on earnings management, audit quality has a negative and insignificant effect on earnings management, foreign ownership structure has a positive and insignificant effect on firm value, audit quality has a positive and significant impact on earnings management. firm value, and earnings management have a positive and significant effect on firm value. This study also found that foreign ownership structure has an indirect effect on firm value through earnings management and audit quality has an indirect effect on firm value through earnings management.